The effect of previous shoulder pain on supraspinatus tendon thickness changes following swimming practice - Porter, K. N.; Blanch, P. D.; Walker, H. M.; Shield, A. J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Objectives: To assess if swimming practice results in changes in supraspinatus tendon thickness, acromiohumeral distance, and occupational ratio in shoulders of elite swimmers with and without a history of shoulder pain. Design: Case-Control study. Methods: A convenience sample of fifty elite swimmers (14-22 years) were recruited for this study. Groups were defined by the presence (history of pain, N = 37) or absence (pain free, N = 63) of significant interfering shoulder pain within the previous 6 months. The current study analyzed supraspinatus tendon thickness, acromiohumeral distance, and the occupational ratio, through the use of ultrasound. Measures were taken prior to swim practice; immediately after practice; and 6 hours post-practice. Results: No statistically significant difference in supraspinatus tendon thickness, acromiohumeral distance or ratio between shoulders with and without a history of pain were found at rest. Following a swimming practice, both shoulders with and without a history of pain had a significant increase in tendon thickness (0.27 & 0.17 mm; P = .001 & <.001). The increase in thickness was significantly greater in the history of pain shoulders compared to pain-free shoulders (P = .003). At 6-hour post-practice, the history of pain shoulders was still significantly thicker than their pre-practice (rested) levels (P = .007). Despite changes in tendon thickness, the occupational ratio remained non-significant between groups. Conclusion: Shoulders with a history of pain show an altered response to swimming practice. The results of the current study have implications for training load and injury management. It should prompt investigation into how the tendon reacts under varying load conditions.